PENGARUH LOKASI TOKO DAN KUALITAS PELAYANAN TERHADAP MINAT BELI KONSUMEN PADA RESTORAN PIZZA HUT METROPOLITAN CITY PANAM KOTA PEKANBARU - Wicaksono, Prayoga Teguh; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to examine the persial and simultaneous influence of store location and service quality on consumer buying interest. Where independent variable in this liresearch is store location and service quality while dependent variable is consumer buying interest. The sample used is secondary data derived consumer count report  in Pizza Hut Restaurant Metropolitan City Panam in Pekanbaru City period 2019.This study uses primary data from Pizza Hut Metropolitan City Panam consumer questionnaire. Samples and sampling using insidental sampling technique. Data analysis using multiple linear regression analysis, t test, F test, and test of coefficient of determination. Data analysis using multiple linear regression analysis with SPSS 20.The results of this study indicate that the variable of store location and service quality in persial (t test) have a significant effect on consumer buying interest at Pizza Hut restaurants metropolitan city panam. The simultaneous test results (F test) shows the influence of store location and service quality on consumer buying interest at Pizza Hut restaurants metropolitan city panam.  Keywords: store location, service quality, and buying interest